Identification and experimental assessment of two-input Preisach model for coupling hysteresis in piezoelectric stack actuators - Dong, Yangyang; Hu, Hong; Wang, Hongjun (Sensors and actuators. A. Physical., 2014)
•We present a complete identifiable procedure for the two-input Preisach model by employing a three-dimension interpolation algorithm based on two databases.•Experimental set-up is established to testify the performance of the model.•By discussing the properties of coupling hysteresis in piezo-actuators, the feasibility of the two-input Preisach model using in hysteresis characterization is confirmed.•Experiments verify the accuracy of the two-input Preisach model for estimating hysteresis in piezoelectric stack actuators that is subject to two inputs: excitation voltage and external load. Piezoelectric stack actuators (PEAs) do not always perform as desired because external loads have an effect on the inclination of the hysteresis loop that causes deterioration of the tracking performance. To take account of this loading factor, the two-input Preisach model (TPM) is introduced to estimate the coupling hysteresis in PEAs for loading applications. This paper tackles the identification problem of TPM using a three-dimension interpolation algorithm based on the first-order reversal curves (FORCs) technique. To prove the feasibility of the TPM in describing piezoelectric hysteresis, the coupling hysteresis properties in PEA via experimental data are discussed. To assess the accuracy of the TPM in predicting expansion in a case where the PEA is subject to two inputs, it is compared with the single-input classical Preisach model (CPM) by performing several experiments under various excitation conditions.